Opportunistic Infections in Patients with HTLV-1 Infection - Toshiki Tanaka; Toshio Sekioka; Masakatsu Usui; Shinsaku Imashuku (Case Reports in Hematology)
As an acquired immunodeficiency, human immunodeficiency virus (HIV) infection is primarily responsible for opportunistic infections in infected patients. However, opportunistic infections also occur in individuals with human T cell lymphotrophic virus type 1 (HTLV-1) infection. Here, we report opportunistic infections in two Japanese HTLV-1-seropositive patients. The first patient was a 67-year-old male, who had cytomegalovirus infection associated with esophagogastritis and terminal ileitis. The patient was HTLV-1-positive and was diagnosed with smoldering adult T cell leukemia (ATL). High levels of serum soluble IL-2 receptor (sIL-2R; 4,304 U/mL) and an increased percentage of CD4+CD25+ T cells (75.5%) in peripheral blood were also detected. The second patient was a 78-year-old female, a known asymptomatic HTLV-1 carrier, who presented with persistent herpes zoster, followed by Pneumocystis jirovecii pneumonia. Disease progression of smoldering ATL along opportunistic infections was observed with very high levels of serum sIL-2R (14,058 U/mL) and an increased percentage of CD4+CD25+ T cells (87.2%) in peripheral blood. In patients with suspected opportunistic infections, both HTLV-1 and HIV should be considered. In HTLV-1-positive patients, an increase in the CD4+CD25+ T cell subset may have its value as a prognostic marker.